Kinetic Resolution of Racemic Mandelic Acid Esters by N, N′‐Dioxide–Scandium‐Complex‐Catalyzed Enantiomer‐Selective Acylation. Issue 48 (5th October 2014) - Zhang, Yuheng; Liu, Xiaohua; Zhou, Lin; Wu, Wangbin; Huang, Tianyu; Liao, Yuting; Lin, Lili; Feng, Xiaoming
Abstract A simple and efficient acylative kinetic resolution of racemic mandelic acid esters was accomplished with a chiral N, N'‐dioxide–scandium(III) complex under mild and base‐free reaction conditions. A variety of mandelic acid esters performed well in the reaction, obtaining both acylated products (up to 49% yield, 97% ee) and recovered substrates (up to 49% yield, 95% ee) in high enantioselectivities with perfect selectivity factors (up to 247). The enantioselective recognition and catalytic models were also proposed for the catalytic KR reaction.